ФОРМИРОВАНИЕ СТРУКТУРЫ РУСЛОВЫХ РАЗВЕТВЛЕНИЙ - Чалов С.Р. (My University, 2006)
The role of external factors in the brided channels formation is analyzed on the base of quantitative criteria. The braided channel classification by flow redistribution is put forward. The correspondence of braided channel structure to river valley and channel morphology is shown.
Keywords: 551.4.436.13->556.51